Metalexicographic criteria for a monolingual descriptive dictionary presenting the standard variety of Yipunu - Tomba Moussavou, Fatima (Stellenbosch : Stellenbosch University, 2012)
Dissertation (DLitt)--University of Stellenbosch, 2007.